2020
DOI: 10.3390/jcm9123994
|View full text |Cite
|
Sign up to set email alerts
|

Pars Plana Vitrectomy and the Risk of Ocular Hypertension and Glaucoma: Where Are We?

Abstract: Purpose is to review the pathogenic mechanism for ocular hypertension and glaucoma development after pars plana vitrectomy. Both acute and chronic causes are considered, and special attention is paid to the theories and clinical evidence on the risk of developing Open Angle Glaucoma (OAG) after Pars Plana Vitrectomy (PPV). Most existing scientific literature on the issue agree on the role of ascorbate as an oxygen scavenger within the vitreous chamber. Oxygen tension in the vitreous and anterior chamber is max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 50 publications
0
23
0
1
Order By: Relevance
“…Studies investigating the effect of removing the vitreous cavity on IOP increases are needed. A previous review by Rossi reported that the causes of chronic IOP increases after vitrectomy are angle synechia (chronic inflammation in the anterior chamber, intermittent closure), neovascularization (secondary to anterior segment ischemia), silicon oil glaucoma, and open-angle glaucoma (oxidative stress increases trabecular resistance) ( 4 ). We speculate that the reason for IOP increases in our cases may be a combination of both chronic inflammation and oxidative stress as described above.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies investigating the effect of removing the vitreous cavity on IOP increases are needed. A previous review by Rossi reported that the causes of chronic IOP increases after vitrectomy are angle synechia (chronic inflammation in the anterior chamber, intermittent closure), neovascularization (secondary to anterior segment ischemia), silicon oil glaucoma, and open-angle glaucoma (oxidative stress increases trabecular resistance) ( 4 ). We speculate that the reason for IOP increases in our cases may be a combination of both chronic inflammation and oxidative stress as described above.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MIVS may be beneficial for patients with glaucoma, especially for those who have undergone filtering surgery. Meanwhile, it has been suggested that the removal of the vitreous itself, regardless of the mode of surgery (MIVS or 20-G system), may result in the increase in intraocular pressure (IOP) (1,2) and glaucoma prevalence (3)(4)(5). The entire mechanism underlying chronic IOP increase after vitrectomy is unknown; however, it may be attributed to the increase in the partial pressure of oxygen (pO 2 ) (3,4,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we included in our study patients who underwent previous surgery other than glaucoma surgery (vitrectomy, keratoplasty). Although pars plana vitrectomy and penetrating keratoplasty could be considered risk factors for ocular hypertension and glaucoma (Rossi & Ripandelli 2020;Gonz alez-P erez et al 2021), a cumulative probability of qualified success of 74% at 10 years after AGV implant was reported in a population of eyes with intractably raised IOP following pars plana vitrectomy (Rabiolo et al 2020). Similarly, a glaucoma drainage device was able to control intractable glaucoma after penetrating keratoplasty in 70% of eyes at 10 years postoperatively (Purtskhvanidze et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive phacoemulsification and vitreous surgery have become widely used and are safely performed for various surgical indications 11 – 13 . However, some surgical complications may occur, and it is well known that elevated IOP can occur after vitrectomy 14 . In addition to the cornea, the sclera, lens, and vitreous are involved in ocular rigidity.…”
Section: Introductionmentioning
confidence: 99%